Organizational model of continuous learning of managers of network educational organizations in the educational environment of institution of postgraduate teacher education - Stoikova, Victoriia (ScienceRise: Pedagogical Education, 2017)
Creation of educational institutions of the new type in Ukrainian educational network (supporting schools with the net of branches) and their associations (educational districts) needs from managerial staff the mastering of grounds of the matrix and network system of the management of educational institutions, and from postgraduate educational institutions – the new approaches to the formation of managerial professional competences. The features of organization of educational environment of postgraduate pedagogical educational institution for continuous teaching of managers of network educational organizations were revealed in the study. The model is built on the andragogical principles of managerial staff professional development. It includes four basic levels: educational institution, educational district, urban district (united territorial community), regional center of education development. The methods of corporative learning, Internet-technologies, cluster approach to the learning process organization, different forms of qualification improvement courses organization (traditional (full-time and full-time-correspondence learning), distant learning, dual learning, prolonged learning, accumulation learning by case-technologies and so on) are widely used in the model. The learning process is realized at a specialist’s main working place of and at a distance from it. The model has the signs of openness, innovation, cascade character, flexibility, variability (electivity and selectivity), matrix character and corresponds to the logistic principle of “knowledge just in time”